Motion Control Strategy for an Electro-hydraulic Control System of a Flying Vehicle - M. Zaki Fadel; M. Galal Rabie; A. M. Youssef (Recent Progress in Science and Technology Vol. 6, 2023)
The use of Fly-by-Wire (FBW) systems for aeronautical vehicle flight control has continuously increased in recent years. These systems employ electro-hydraulic servo-actuators to position the movable thrust vector controls on spacecraft or airplanes maneuvering surfaces. Electronics and hydraulic power systems have been combined to provide a variety of strong and accurate control systems that save a significant amount of energy and money. In this study, a comprehensive nonlinear mathematical model and a computer simulation program using the MATLAB/SIMULINK package are used to control the motion of an aircraft integrated electro-hydraulic servo-actuator (ISA). The ISA is primarily made up of two distinct active hydraulic power systems that provide it with the necessary power. The investigated ISA includes a twin-symmetrical hydraulic actuation cylinder, two electro-hydraulic servo-valves, and a cleverly constructed set of built-in directional control valves with a feedback system. By obtaining the transient response of the ISA, the output linear motion of the actuating cylinder of the ISA is provided and regulated. By altering the system control settings, a traditional PID controller is created and tuned using Zeigler-approach Nichol’s in accordance with the Integral Square Error (ISE) criteria to minimize the difference between the required system output feedback and the desired set input. By using the tuned PID controller, the system’s stability and precision needs are guaranteed.